Growth, physiological and biochemical responses of winged bean (Psophocarpus tetragonolobus) towards different shade levels / Murthazar Naim Raai - Murthazar Naim , Raai (2020)
Ambiguous evidence suggests that shade could regulate the indeterminate growth habit of winged bean (Psophocarpus tetragonolobus), an underutilized protein-rich legume from the tropics. This study was conducted to examine the effects of three different shade levels, including 60% (heavy shade), 30% (moderate shade), and 0% (as control) on 25 traits associated with morphological features, photosynthetic and agronomic characteristics of winged bean. The shade-house experiment was conducted using a completely randomized design. Collectively, approximately 80% of the studied variables displayed significant differences (P<0.05) between at least two shade treatments. Shading generally showed the most pronounced effect on the physiological traits of the legume, whereby the stomatal conductance, photosynthetic and transpiration rates differed significantly (P<0.05) among plants for all treatments. Overall, non-shaded plants were observed to have superior growth and physiological responses than the shaded plants, especially being significantly taller with higher stomatal conductance, photosynthetic and transpiration rates. Interestingly, the moderately shaded plants exhibited the highest yield per plant (28.9 g } 1.47), which significantly differed from the non-shaded (23.8 g } 1.06) and heavily shaded (21.4 g } 1.48) plants. These findings suggested that winged bean plants can adapt to partial shaded conditions or canopy cover, making it a potential nitrogen-fixing cash crop which can be planted together with fruit and oil trees in commercial plantations. Given that there were no significant differences between the moderately shaded and heavily plants with respect to their seed protein content (P>0.05), this project also demonstrates that winged bean can grow and yield well while maintaining its protein content under moderately shaded condition.